A new two-scroll chaotic system with two nonlinearities: dynamical analysis and circuit simulation - Sundarapandian Vaidyanathan; Aceng Sambas; Sen Zhang; Yicheng Zeng; Mohamad Afendee Mohamed; Mustafa Mamat (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Chaos theory has several applications in science and engineering. In this work, we announce a new two-scroll chaotic system with two nonlinearities. The dynamical properties of the system such as dissipativity, equilibrium points, Lyapunov exponents, Kaplan-Yorke dimension and bifurcation diagram are explored in detail. The presence of coexisting chaotic attractors, coexisting chaotic and periodic attractors in the system is also investigated. In addition, the offset boosting of a variable in the new chaotic system is achieved by adding a single controlled constant. It is shown that the new chaotic system has rotation symmetry about the z-axis. An electronic circuit simulation of the new two-scroll chaotic system is built using Multisim to check the feasibility of the theoretical model.